Blood biomarkers associated with acute type II respiratory failure in COPD: A meta‐analysis. (10th January 2022) - Shi, Tieying; Feng, Li
Abstract: Objective: This study aims to summarize the risk factors of type II respiratory failure in patients with an acute exacerbation of chronic obstructive pulmonary disease (COPD), to guide clinical treatment in time, and consequently reduce the serious impact of COPD on human health. Methods: Five databases were searched for relevant articles on risk factors of acute exacerbation of COPD combinate with type II respiratory failure. We calculated the standard mean difference (SMD), odds ratio (OR), and their 95% confidence interval (95% CI) utilizing a fixed‐effect model or a random‐effect model according to the level of heterogeneity. Results: As of 14 May 2021, 13 articles were included in our meta‐analysis. The results showed that low albumin and uric acid levels were the risk factors for type II respiratory failure in acute exacerbation of COPD patients, and the differences were statistically significant (albumin: SMD = −2.03, 95% CI: −2.81, −1.26; uric acid: SMD = −1.28, 95% CI: −1.41, −1.15). Besides, 10 other systematic markers have been reported to be the risk factors for type II respiratory failure of patients with acute exacerbation of COPD, but only in single study. Conclusion: The meta‐analysis results further confirm that low albumin and uric acid levels are risk factors for type II respiratory failure in acute exacerbation of COPD patients. Additionally, this analysis also summarizes many emerging inflammatory indicators, nutritional indicator, and cardiovascular system indicators to predict the progression of acute exacerbation of COPD to type II respiratory failure but only in single study.